EVALUATION OF MADURA LANGUAGE TEXTBOOKS AT ELEMENTARY SCHOOL LEVEL - M. Khoiri; H. Harsono; K. Kusyairi (Universitas Sembilanbelas November Kolaka, 2018)
The purpose of this study was to find out information and describe the quality of Madurese language textbooks both in terms of content, presentation, and language. The type of this research is evaluation research, namely by conducting an elementary level Madura language curriculum document study (syllabus) and research instruments provided to students and material experts. The results of the study showed that students' responses to Madurese language textbooks at the elementary level included a very good category, which was 80.86. While the results of the validation of material experts state that Madurese language textbooks are in a valid category and can be used but need minor revisions, ie with a value of 80.60.